A study on the low-cost Digital Elevation Model (DEM) surface measurement of landslide monitoring by close range photogrammetry / Munirah Radin Mohd Mokhtar, Mohd Najib Husain and Asmma' Che Kasim - Mohd Mokhtar, Munirah Radin; Husain, Mohd Najib; Che Kasim, Asmma' (2021)
This paper presents the preliminary results on a simulation study on the production of a low-cost Digital Elevation Model (DEM) on thelandslide study area in Seri Iskandar, Perak. The main objective of this paper is to present the potentiality of Close Range Photogrammetry (CRP) as a data acquisition tool in producingDigital Elevation Model (DEM) by using data from thesurface measurement. This method was applied using stereopairs photographs captured data from the ground level detection or known as close-range photogrammetry with the use of a digital camera mounted on a tripod as a tool for data collection. Close Range Photogrammetry (CRP) applications are useful for mapping of thearea that is difficult and risky to point manpower on terrain that consists of steep and dangerous slopes. Conventional methods require measurements using Electronic Distance Measuring (EDM), but this method is very costly and needs a survey team placed on land site area. The research data were carried out with two different epoch data. The result proves that CRP can produce DEM at less cost compared to other methods.